Effect of composite collagen containing hydrogel on the functional activity of fibroblasts after acid-induced in vitro injury - P. A. Markov; P. S. Eremin; I. R. Gilmutdinova; A. I. Greben; E. Yu. Kostromina; А. S. Sokolov; I. A. Artemyeva (Acta Biomedica Scientifica)
It is well known that the acidity of the microenvironment has a significant impact on the functional activity of cells involved in tissue repair. To date, the effect of biomaterials containing components of the human dermis intercellular matrix on fibroblasts under acidosis has not been fully studied.The aim of the study. To evaluate the effect of a composite hydrogel containing dermal components on the functional activity of intact fibroblasts and fibroblasts with acid-induced dysfunction.Materials and methods. To simulate the physicochemical conditions of acute inflammation, human fibroblasts were incubated for an hour at 39 °C in a nutrient medium overacidified to pH = 6. The morphometric characteristics of human skin fibroblasts were assessed using light and fluorescence microscopy methods. The number of apoptotic cells and proliferation index were assessed using flow cytometry.Results. It has been established that exposure of fibroblasts to an acidic medium inhibits their adhesive properties and reduces the rate of cell growth. The introduction of hydrogel into a cell suspension with damaged cells restores adhesive properties and cell growth. In the fibroblast population, after acid exposure, the number of living cells decreases, and the number of apoptotic cells increases. Cultivation of damaged fibroblasts in the presence of a composite hydrogel increases the number of living cells in the population and reduces the number of apoptotic cells. Acid-induced fibroblast damage reduces the proliferative activity index. It was revealed that the introduction of hydrogel into the culture medium stimulates the proliferative activity of both intact and damaged fibroblasts. The results obtained indicate that a composite hydrogel consisting of extracellular matrix components is capable of restoring the functional activity of fibroblasts damaged as a result of exposure to an acidic medium. The results obtained can be used to create biomaterials that increase the efficiency of skin regeneration in cases of excessively intense acute inflammation.